Risk of Skin Cancer in Workers Exposed to Diesel Exhaust: A Systematic Review and Meta-Analysis of Cohort Studies - D'Agostini, Marika; Collatuzzo, Giulia; Teglia, Federica; Boffetta, Paolo (La Medicina del Lavoro, 2024)
Background: Our objective was to study the association between occupational exposure to diesel exhaust (DE) and skin cancer. Methods: A systematic review following STROBE guidelines and PECOS criteria was conducted to identify cohort studies describing the association between occupational DE exposure and the risk of skin cancer. We extracted 12 independent risk estimates for melanoma skin cancer (MSC), 8 for non-melanoma skin cancer (NMSC), and 3 for skin cancer not otherwise specified (SC-NOS). Random effects meta-analyses were performed, site-specific and stratified by geographic region and quality score. 95% confidence intervals (CI) were reported. Between-study heterogeneity and potential publication bias were investigated. Results: There was no overall evidence of an increased risk of MSC [RR=0.90, 95% CI: 0.73-1.11; I2=92.86%, 95% CI: 82.83-97.03%], NMSC [RR=1.04, 95% CI: 0.88-1.23; I2=60.79%, 95% CI: 0-87.34%] or SC-NOS [RR=0.72, 95% CI: 0.54-0.97; I2=26.60%, 95% CI: 0-94.87%] in workers exposed to DE. No difference between low-quality and high-quality studies was found. A stratified analysis by geographical region did not reveal any significant differences. There was no evidence of publication bias. Conclusions: No evidence of an association between skin cancer and occupational DE exposure was found. Residual confounding and other sources of bias cannot be ruled out.